2011
DOI: 10.1017/s0022377810000747
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the bump-on-tail instability in compressing plasma

Abstract: Through particle-in-cell simulations, the evolution of the bump-on-tail instability (BoTI) is studied for plasma subject to one-dimensional mechanical compression. It is shown that the final state of BoTI differs from that described by quasilinear theory for stationary bulk plasma and can depend on the compression history. The transformation of thermal energy into wave energy increases the plasma compressibility, thereby decreasing the amount of mechanical work required to compress the plasma to a specified si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Recently, however, a number of studies [11][12][13][14][15] of waveparticle interactions in nonstationary plasmas has revealed previously unexplored phenomenology and potentially useful mechanisms. Such phenomena are intrinsically non-steady-state, and hence require a modification of the methods typically used to analyze and describe the physics in stationary systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, a number of studies [11][12][13][14][15] of waveparticle interactions in nonstationary plasmas has revealed previously unexplored phenomenology and potentially useful mechanisms. Such phenomena are intrinsically non-steady-state, and hence require a modification of the methods typically used to analyze and describe the physics in stationary systems.…”
Section: Introductionmentioning
confidence: 99%
“…Such phenomena are intrinsically non-steady-state, and hence require a modification of the methods typically used to analyze and describe the physics in stationary systems. In particular, References [11][12][13][14][15] focus primarily on non-steady-state effects associated with expanding or compressing plasma. When a wave is embedded in such a nonstationary plasma and is undamped initially, modification of the bulk plasma parameters through the nonstationary processes changes the wave dynamics and can lead to an induced waveparticle resonance with the fast-particles on the tail of the bulk plasma distribution [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, waves might be amplified through compression 4 and then damp resonantly on a particular species in a switchlike manner at a predetermined moment. 5 It was also suggested that concentrating energy in a compressing plasma in the form of waves can increase the plasma effective compressibility, 6 and recent work 7 has even described the basic thermodynamic cycles whereby the interplay between plasma wave energy and thermal energy could be utilized to construct a plasma heat pump and heat engine. Yet, these studies were focused primarily on linear waves, whereas practical applications may require higher wave amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to study such nonlinear effects for wave evolution in one-dimensional (1D) collisionless plasmas undergoing compression, within a paradigmatic model 5,6 of a bounded system with moving walls. Specifically, addressed here is the evolution of electrostatic Bernstein-Greene-Kruskal (BGK) modes, 8 which are produced as saturated states of a bump-on-tail instability, like in unbounded plasmas.…”
Section: Introductionmentioning
confidence: 99%